2020
DOI: 10.1371/journal.pone.0238699
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and associated occupational stresses among Chinese nurses: A cross-sectional study in three hospitals

Abstract: Background There is literature scarcity relating to burnout and other work stresses in relation to Chinese nursing-workforce performance. Objectives To assess the relationship between self-esteem versus burnout; and effort-reward ratio versus favorability to the work environment, among Chinese nurses. Methods We employed four validated questionnaires in the assessment burnout, self-esteem, effortreward ratio, and favorability of nursing workplace; Maslach-Burnout Inventory (MBI), Rosenberg's self-esteem (RS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Studies have shown that Chinese nurses are emotionally drained and feel a depletion of psychological resources [15]. Being in a position of power and authority, leaders can provide this psychological safety resource to keep them calm and committed [16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Chinese nurses are emotionally drained and feel a depletion of psychological resources [15]. Being in a position of power and authority, leaders can provide this psychological safety resource to keep them calm and committed [16].…”
Section: Introductionmentioning
confidence: 99%
“…Nursing is considered a stressful profession because it is closely related to high expectations job needs and demands, particularly throughout the COVID‐19 pandemic when about two‐thirds of the nurses suffered from high degrees of stress (Abuatiq & Borchardt, 2021; Babapour et al, 2022; Kabakleh et al, 2020). Regarding nurses working at public health‐care centres (PHCCs), 40% of public health nurses (PHNs) were found to have a high OS, which made them dissatisfied with the job (Dehdashti et al, 2018; Shen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nursing is considered a stressful profession because it is closely related to high expectations job needs and demands, particularly throughout the COVID-19 pandemic when about two-thirds of the nurses suffered from high degrees of stress (Abuatiq & Borchardt, 2021;Babapour et al, 2022;Kabakleh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%